TUBUH DAN JILBAB: ANTARA DIRI DAN ‘LIYAN’ - Titik Rahayu; Siti Fathonah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2016)
Wearing jilbab as an obligation of the religious teaching is not the only reason for Muslim women to wear it. There are many factors that cause someone wearing jilbab. It can be from internal and also external factors. The internal factor comes from individual’s awareness to implement syariat, whereas the external factors come from motivation from closely related persons, existing regulation of wearing jilbab, and also environmental influence. At the early process of wearing jilbab, there are that influence someone’s decision to wear jilbab. The resistance from within (self-resistance) is mind pressure felt by someone faced change. Whereas resistance coming from outside, can be from family, negative response of the society, and the unsupported environment.